2022
DOI: 10.1007/s13300-022-01237-9
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Glycaemic Control of Dapagliflozin: Microangiopathy and Non-classical Complications

Abstract: Dapagliflozin is a selective sodium-glucose cotransporter 2 inhibitor (SGLT2i) indicated for the treatment of type 2 diabetes mellitus (T2DM), heart failure (HF) with reduced ejection fraction (EF) and chronic kidney disease (CKD). In monotherapy or as an additive therapy, dapagliflozin aids glycaemic control, is associated with reductions in blood pressure and weight, and promotes a favourable lipid profile. In this review, we address the impact of dapagliflozin on cardiovascular risk factors and common micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Mechanistically, SGLT2 inhibitors including dapagliflozin can reduce the maximum carrying capacity of tubular glucose absorption, which raises urine glucose excretion and lowers plasma glucose levels. In addition to their hypoglycemic actions, SGLT2 inhibitors have been demonstrated to offer blood pressure lower effects [ 3 , 4 , 5 ], weight-loss [ 6 , 7 ], and cardioprotective benefits [ 6 , 8 , 9 ] and to enhance glucose metabolism in epicardial fat [ 10 ]. Furthermore, dapagliflozin may improve lipoprotein profile and atherosclerosis development [ 11 ], in contrast to empagliflozin that raises low-density lipoprotein cholesterol levels [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, SGLT2 inhibitors including dapagliflozin can reduce the maximum carrying capacity of tubular glucose absorption, which raises urine glucose excretion and lowers plasma glucose levels. In addition to their hypoglycemic actions, SGLT2 inhibitors have been demonstrated to offer blood pressure lower effects [ 3 , 4 , 5 ], weight-loss [ 6 , 7 ], and cardioprotective benefits [ 6 , 8 , 9 ] and to enhance glucose metabolism in epicardial fat [ 10 ]. Furthermore, dapagliflozin may improve lipoprotein profile and atherosclerosis development [ 11 ], in contrast to empagliflozin that raises low-density lipoprotein cholesterol levels [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…30 Using Canadian data, we report that visual impairment prevalence decreased among people with and without diabetes from 1994 to 2014, irrespective of their level of education and income. The decreased visual impairment prevalence likely reflects the collective efforts by clinicians, researchers, the public and government to prevent vision loss, including better understanding of diabetic eye diseases, [31][32][33] better bloodglucose control, [34][35][36][37][38] recent effective treatment for advanced diabetic retinopathy and technology (e.g., optical coherence tomography) for early detection of diabetic retinal pathologies, [39][40][41][42][43][44] government coverage for new advancements and various initiatives for increased diabetic eye screening. [45][46][47] Our results are also in accordance with studies that reported a significantly higher visual impairment prevalence among people with diabetes than those without.…”
Section: Discussionmentioning
confidence: 99%
“…Shih-Ting Huang 1,2,3, † , Pei-Jane Bair 3,4, † , Shih-Sheng Chang 3,5 , Yu-Nong Kao 1,3 , San-Ni Chen 6 , I-Kang Wang 3,4 , Chih-Wei Chiu 1 , Chi-Tzung Chang 3 , Ying-Hsiu Shih 7 , Chi-Yuan Li 4 and Tung-Min Yu 1,3,4, * Diabetic retinopathy (DR) accounts for 80% of cases of vision loss in patients with type 2 diabetes mellitus (T2DM). Interventional treatments are only indicated in advanced DR and are ineffective in some patients.…”
Section: Risk Of Diabetic Retinopathy In Patients With Type 2 Diabete...mentioning
confidence: 99%
“…In addition to remarkable effect of cardiorenal protection, SGLT2is have been considered having additional benefits in various diabetic complications, such as macular edema, cognitive impairment, and nonalcoholic fatty liver disease. 6 SGLT2is and dipeptidyl peptidase-4 inhibitors (DPP4is) are both recommended as second-line, add-on oral hypoglycemia medications in uncomplicated patients with diabetes. 7 A meta-analysis comparing the efficacy and safety of SGLT2is and DPP4is revealed that SGLT2is plus metformin was associated with a more significant decrease in fasting plasma glucose than was DPP4is plus metformin.…”
Section: Risk Of Diabetic Retinopathy In Patients With Type 2 Diabete...mentioning
confidence: 99%
See 1 more Smart Citation